Tailoring Electronic and Optical Properties of MXenes through Forming Solid Solutions - Han, Meikang; Maleski, Kathleen; Shuck, Christopher Eugene; Yang, Yizhou; Glazar, James T; Foucher, Alexandre C; Hantanasirisakul, Kanit; Sarycheva, Asia; Frey, Nathan C; May, Steven J; Shenoy, Vivek B; Stach, Eric A; et al. (Journal of the American Chemical Society, 2020)
Alloying is a long-established strategy to tailor properties of metals for specific applications, thus retaining or enhancing the principal elemental characteristics while offering additional functionality from the added elements. We propose a similar approach to the control of properties of two-dimensional transition metal carbides known as MXenes. MXenes (M n+1X n ) have two sites for compositional variation: elemental substitution on both the metal (M) and carbon/nitrogen (X) sites presents promising routes for tailoring the chemical, optical, electronic, or mechanical properties of MXenes. Herein, we systematically investigated three interrelated binary solid-solution MXene systems based on Ti, Nb, and/or V at the M-site in a M2XT x structure (Ti2‑yNb y CT x , Ti2‑yV y CT x , and V2‑yNb y CT x , where T x stands for surface terminations) showing the evolution of electronic and optical properties as a function of composition. All three MXene systems show unlimited solubility and random distribution of metal elements in the metal sublattice. Optically, the MXene systems are tailorable in a nonlinear fashion, with absorption peaks from ultraviolet to near-infrared wavelength. The macroscopic electrical conductivity of solid solution MXenes can be controllably varied over 3 orders of magnitude at room temperature and 6 orders of magnitude from 10 to 300 K. This work greatly increases the number of nonstoichiometric MXenes reported to date and opens avenues for controlling physical properties of different MXenes with a limitless number of compositions possible through M-site solid solutions.